Digital mental health education: the impact of e-book intervention on anxiety knowledge among adolescent girls - Irmawati S; Fanny Fatimah Mayasari Masdar; Rosdianah; Muh.Yunus (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2025)
Introduction: Adolescence is a critical developmental stage often accompanied by psychological challenges, with anxiety being one of the most prevalent mental health issues among young people. Limited awareness and ineffective learning strategies contribute to poor understanding of anxiety, particularly among adolescent girls. This study aimed to examine the effect of e-book media on improving knowledge about anxiety and mental health among adolescent girls. Methods: A pre-experimental study with a one-group pretest–posttest design was conducted among 62 female students at Madrasah Aliyah Muhammadiyah Salaka, South Sulawesi, Indonesia. Data were collected using a validated questionnaire assessing knowledge of anxiety before and after the intervention. The educational e-book contained comprehensive information on the definition, causes, symptoms, prevention, and coping strategies related to anxiety. Data were analyzed using the Wilcoxon Signed Rank Test with SPSS version 29.0. Results: Before the intervention, 54.8% of respondents demonstrated low knowledge, while 4.8% had high knowledge. After exposure to the e-book, 74.2% reached the high knowledge level, and none remained in the low category. Statistical analysis revealed a significant difference between the pretest and posttest results (Z = -6.997, p < 0.0001), confirming the effectiveness of e-book media in enhancing mental health knowledge. Conclusion: E-book media proved to be an effective and innovative educational tool for improving adolescents’ understanding of anxiety and mental health. Integrating digital learning materials into school-based programs can promote mental health literacy and support early prevention among youth populations.